Analysis of Household Cigarette Demand with Almost Ideal Demand System (AIDS) Model on the Island of Java - Tambunan, Catherin Yensiska Mutiara; Afiatno, Bambang Eko (Jurnal Ilmu Ekonomi Terapan, 2025)
This study aims to analyze the effect of household expenditure, cigarette prices, and food and beverage prices on household cigarette consumption in six provinces in Java using data from the 2021 National Socio-Economic Survey (SUSENAS). The results of this study are expected to help the authorities in formulating policies related to cigarette consumption, which has been a topic of debate. Almost Ideal Demand System (AIDS) is an econometric method used to analyze consumer behavior and estimate the elasticity of demand with respect to variations of price and expenditure. The AIDS model has a good ability to predict consumer response to changes in price and expenditure. Ordinary Least Square (OLS) was chosen as the estimation method used to produce parameters for the effect of own price, cross-price, and consumer expenditure on the portion of household expenditure on cigarette consumption. As a comparison, this study used food and beverage commodities for cross-price measurement. The results showed that cigarette prices, food and beverage commodity prices, and food and beverage expenditure had a significant effect on the portion of household expenditure on cigarette consumption. Measurement of price elasticity shows that the portion of cigarette expenditure is inelastic to changes in cigarette prices. Cross price elasticity indicates that cigarettes are complementary goods with other food and beverage commodities. As for expenditure elasticity, cigarettes can be categorized as normal goods. Cigarette’s price inelasticity indicates that the objective of an excise tax increase to reduce consumption is ineffective. Other than raising taxes, there are other ways to reduce cigarette consumption that should be taken into account. Revenues from cigarette excise and taxes can be allocated to support the provision of better health services. Local government should search for alternative sources of income apart from the tobacco industry